Shared flow and emotional synchrony through group instrumental improvisation: a feasibility study of music-based social connection - Roth, Edward A. (Frontiers in Psychiatry, 2025)
This feasibility and pilot study explored how group instrumental improvisation may foster emotional synchrony and shared flow, constructs linked with trust, bonding, and psychological well-being, and its therapeutic potential in mental health settings. Eight young adult participants, grouped by gender and musical background, engaged in two interactive conditions: instrumental music improvisation using digital mallet percussion instruments and a matched verbal improvisation task. Emotional synchrony and shared flow were assessed via validated scales and complemented by semi-structured group interviews to further capture participants’ experiences. All participants completed the full protocol, demonstrating the study’s procedural feasibility. Quantitative results indicated consistently high levels of shared flow and emotional synchrony across both conditions, with minimal differences between musicians and non-musicians. Qualitative findings highlighted participants’ sense of connection, attunement, and increased group cohesion, especially during musical interaction. Notably, musically inexperienced participants reported feeling connected and engaged despite no prior training, suggesting that structured improvisation may offer a low-barrier entry point for social connection in clinical settings. Feasibility of the study’s design is promising, as are the findings toward therapeutic applications in settings addressing social isolation, anxiety, or addiction recovery, where shared flow and bonding may serve as mechanisms of change.